Sprouting and yield of yam (Diocorea spp.) minisetts in relation to sett size, soil moisture and agroecology - Ayankanmi, T.G.; Shiwachi, H.; Asiedu, Robert (Wiley, 2005)
Seed tuber production of Dioscorea rotundata using the minisett technique was tested on-farm and on-station in different agro-ecological zones in Nigeria. A lower sprouting rate of minisetts was observed in the southern Guinea savanna than in the tropical forest zone. Sprouting and tuber yield in direct field planting of minisetts was strongly influenced by variety of D. rotundata, but D. alata was less affected by sett size. An increase in minisett size in some varieties of D. rotundata would enhance their sprouting potential.